Assessing CO2 storage capacity in the Dalders Monocline of the Baltic Sea Basin using dynamic models of varying complexity. (December 2015) - Yang, Zhibing; Tian, Liang; Jung, Byeongju; Joodaki, Saba; Fagerlund, Fritjof; Pasquali, Riccardo; Vernon, Richard; O'Neill, Nicholas; Niemi, Auli
Highlights: First dynamic modeling study of CO2 geological storage in the Baltic Sea basin. Dynamic modeling approaches of varying complexity are employed. The dominant constraint for capacity is identified and the capacity is estimated. Abstract: The first dynamic modeling study of CO2 geological storage in the Baltic Sea basin is presented. The focus has been on the southern part of the Dalders Monocline. The objective is to get order-of-magnitude estimates of the behavior of the formations during potential industrial scale CO2 injection and subsequent storage periods, with an emphasis on two important aspects of CO2 storage: the injection-induced pressure impact and the long-term upslope migration. In order to maximize the confidence in the model predictions, this work employs a set of different modeling approaches of varying complexity, including a semi-analytical model, a sharp-interface vertical equilibrium (VE) model and a TOUGH2-ECO2N model. The semi-analytical model provides fast estimation of the pressure buildup as well as its sensitivity to variation of the reservoir parameters. Given a certain pressure threshold, a maximum injection rate is estimated from the semi-analytical model and is then fed to the numerical models. The pressure buildup predicted by the numerical models fall close to that by the semi-analytical solution. Extensive modeling of the post-injection upslope migration and trapping evolution together with sensitivity analysis suggests that it is unlikely for CO2 to leak through the north end of the formation. Under the currently considered scenario, the dominant constraint for the storage capacity is the pressure buildup. The pressure limited capacity ( C p ) of the southern Dalders Monocline for the scenario studied here is estimated to be about 100 Mt for a 50-year injection duration. C p is found to increase with permeability as C p  ∼  k 0.926 . Given the knowledge of the dominant constraint for capacity, storage optimization can be specifically targeted on the injectivity issue and operational strategies can be designed to relieve the pressure buildup (e.g., by adding brine production wells, using horizontal wells).